The efficacy of the lactate threshold: a sex-based comparison - Hoffmann, S. M.; Skinner, T. L.; van Rosendal, S. P.; Osborne, M. A.; Emmerton, L. M.; Jenkins, D. G. (The Journal of Strength and Conditioning Research, 2020)
The second lactate threshold (LT2) has previously been associated with endurance performance; however, comparisons between sexes are lacking regarding its efficacy. The aim of this study was to compare LT2 between men and women, specifically regarding its (a) relationship with endurance performance and (b) capacity to establish training and competition intensities. Competitive male (mean ± SD: age, 27.7 ± 4.7 years; VO2max, 59.7 ± 5.2 ml/kg/min; n = 10) and female (mean ± SD: age, 27.3 ± 6.2 years; VO2max, 54.5 ± 5.3 ml/kg/min; n = 12) cyclists and triathletes completed an incremental cycle trial to volitional fatigue (for determination of VO2max and LT2 via the modified D-max method), a constant load (±5%) exercise trial of 30 minutes at LT2 power output, and a 40-km cycle time trial. The LT2 significantly correlated with 40-km cycling performance in both men (r = -0.69 to -0.77; p < 0.01-0.05) and women (r = -0.63 to -0.75; p < 0.01-0.05). All men sustained LT2 power output for 30 minutes, compared with 82% of women. Despite LT2 reflecting a similar heart rate, VO2, and [La-] to those elicited during a 40-km time trial in both men and women, power output at LT2 was 6% higher (p < 0.05) than mean time trial power output in women, with no significant difference in men. Based on these findings, sex-specific recommendations have been suggested in regard to the use of LT2 for establishing performance potential, prescribing endurance training intensities and setting 40-km performance intensity.